Assessment of Bisphenol A in Some Aquatic Food Samples from Eti-Osa Area of Lagos - Lere-Aliu, Moromade; Akpambang, V. O. E; Opatola, S. F (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2025)
Aquatic organisms, being one of the most abundant groups in the aquatic ecosystem are sometimes exposed to all sorts of environmental assaults. These assaults can have serious effects on the nutritive quality of aquatic organisms inhabiting the contaminated aquatic environment. Thus, this study investigated the level of Bisphenol A (BPA) and estimated risk assessment in crayfish, shrimp, periwinkle and crabs obtained from Eti Osa in Lagos Nigeria. The samples were analyzed using solvent extraction, separation and quantitation by gas Chromatography- mass spectrometric method. The recovery value for BPA in the method was 89% with relative standard deviation of 3%. The concentration of Bisphenol A ranged from 0.012 mg/kg to 0.245 mg/kg. Crayfish has the highest concentration of Bisphenol A while periwinkle has the lowest concentration of Bisphenol A. The concentration of Bisphenol A followed this order crayfish > shrimp > crabs > Periwinkle. The concentrations of crayfish is higher than the European Food Safety Authority Specific Migration Limit (SML) of 0.006 mg/kg in food sample while the concentration of crayfish is within the limit set by European Food Safety Authority Specific Migration Limit (SML) 10. Also, The US environmental protection agency (USEPA) has established the tolerable daily intakes (TDI) for BPA at 0.8 mg/kg-bw/day. Contamination from aquatic environment is a major source of BPA exposure to aquatic organisms and the samples analyzed in this work maybe therefore, of a potential health concern to the consumers particularly for vulnerable population groups after a long term consumption hence there is need for regular monitoring of our aquatic environment.